Determinants of growth in the central and eastern European EU member states - a production function approach - Olga Arratibel; Frigyes Ferdinand Heinz; Reiner Martin; Marcin Przybyla; Lucasz Rawdanowicz; Roberta Serafini; Tina Zumer (European Central Bank (ECB), 2007)
Overall, the prospects for a continued and reasonably fast real convergence process between the EU8 countries and the euro area are good. However, the continuation of the rapid progress made by many EU8 countries in the past cannot be taken for granted. In fact, in order to ensure that fast economic growth in the EU8 countries remains sustainable, it is crucial for these economies to take appropriate policy action. First it is important to recall that sound macroeconomic policies including credible monetary policy and appropriate fiscal policy are essential to ensure the appropriate framework conditions for further growth and convergence. Second, they need to address structural labour market problems, in particular by reducing regional and skill mismatches. Third, they must make further efforts to improve the business environment, in order to ensure that the capital accumulation process continues and R&D investments increase. Many of the above-mentioned facets of growth-enhancing policy will also help to ensure a continued inflow of foreign direct investment (FDI), which in turn is expected to help accelerate the convergence process.
Keywords: 330; Wirtschaftswachstum; Produktionsfunktion; EU-Mitgliedschaft